Psychophysiological responses to sedative music in patients awaiting cardiac catheterization examination: a randomized controlled trial - Chang, Hui-Kuan; Peng, Tai-Chu; Wang, Ji-Hung; Lai, Hui-Ling (The Journal of cardiovascular nursing, 2011)
Cardiovascular diseases are the number 1 cause of death globally. Cardiac catheterization is a key step in the diagnosis and management of cardiovascular diseases. Decreasing the stress of cardiac catheterization is a key factor in improving patients' well-being. The aim of the study was to explore the effect of music on psychophysiological indices in patients awaiting cardiac catheterization examination. Using a 2-group repeated-measures design, 54 subjects aged 47 to 70 years and scheduled for cardiac catheterization examination were recruited. The subjects were randomly assigned to either the music group (27 subjects) or the usual-care group (27 subjects). Subjects in the music group listened to 30 minutes of music, whereas the usual-care group rested quietly, as in routine care. The heart rate (HR), HR variability, and skin temperature (ST) were measured at 7 time points and were recorded by the MP150 recording system (BIOPAC Systems, Inc, Goleta, California). Heart rate variability was analyzed by power spectral analysis: low frequency, high frequency, and ratio of low frequency to high frequency. The state of anxiety was measured at baseline and at time 7. At the end of the study, the subjects' music preference was evaluated using a visual analog scale. Listening to music resulted in a significantly reduced state of anxiety (P = .003). Both the music and quiet rest groups noted the beneficial effects of decreased HR and increased ST (all P < .001). The treatment effects of both interventions on HR variability were inconclusive. Moreover, we also found that the higher the scores of the music preference, the lower the subjects' perceived anxiety level (P = .05). Our findings provide the necessary scientific support for the use of sedative music and quiet rest as safe and effective interventions against anxiety, as manifested in the subjects' anxiety state, HR, and ST.